Pendampingan Edukatif Wali Murid dalam Memahami Multiple Intelligences sebagai Fondasi Pendidikan Anak di Sekolah Dasar Islam - Viki Bayu Mahendra; Aditya Fajri Kurnia Pradana; Ashabil Yaqin (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community engagement program was initiated in response to the predominance of academically oriented perceptions among parents regarding children’s intelligence, which tend to limit the recognition of children’s potential to cognitive achievement alone. The program aimed to enhance parents’ literacy and awareness of the Multiple Intelligences framework as a foundational basis for holistic child education in an Islamic elementary school context. A Participatory Action Research (PAR) approach was employed, encompassing participatory planning, conceptual socialization sessions, child potential mapping workshops, collective reflection, and continuous evaluation. The findings highlight substantive outcomes. Parents experienced a significant paradigm shift in understanding the diversity of children’s intelligences, moving from a single-dimensional academic perspective toward a more comprehensive and appreciative view of individual potential. Parenting practices became more supportive, dialogical, and less comparative. In addition, a parents’ communication forum emerged as a new social institution within the school community, accompanied by the rise of local leadership that contributes to program sustainability. These results demonstrate that educational mentoring grounded in the Multiple Intelligences framework effectively promotes social transformation in Islamic elementary education through strengthened collaboration between school and family.